Geomechanical approximation using wave velocities and their relationship with the parameter “b” - Espinoza, Peter (2024)
In this research, an exhaustive and rigorous analysis about microseismicity and its importance for the analysis of geological structures will be presented, with special attention on the application of the GSI table and its relationship with safety. Microseismicity is the technique of detection and analysis of small seismic events that occur during the advance and mining exploitation, and its study is fundamental to guarantee a safe and efficient operation. The presence of these seismic events indicates the existence of stresses and deformations in the geological structures, which can have a significant impact on the safety of the operation. Therefore, microseismicity monitoring is an essential tool for geomechanical risk management. In this thesis the relationship between microseismicity and geological structures will be explored, using the GSI table as an important tool for the interpretation of microseismic data. The GSI table is a tool developed by the International Society for Rock Mechanics to assess the geomechanical stability of rock structures. In this work, the microseismic data will be analyzed and correlated with the GSI table, which will allow a better understanding of the geomechanical characteristics of the mine and a more accurate evaluation of geomechanical risk.